Remote blood pressure monitoring with a wearable photoplethysmographic device in patients undergoing coronary angiography: the senbiosys substudy. Issue 6 (8th August 2022) - Schukraft, Sara; Haddad, Serj; Faucherre, Yannick; Arroyo, Diego; Togni, Mario; Barison, Anthony; Boukhayma, Assim; Cook, Stéphane; Caizzone, Antonino
Abstract : Aims: The purpose of this study is to evaluate the accuracy of the Senbiosys device in measuring blood pressure (BP) by photoplethysmography (PPG) in patients undergoing coronary angiography. Methods: This is a substudy within the Senbiosys trial, which is a prospective, single-arm, single-center study, evaluating the accuracy of BP estimation of the Senbiosys device compared to invasive BP. Patients referred for coronary angiography underwent invasive BP measurement and simultaneously wore the Senbiosys ring. SBP and DBP estimations measured by the Senbiosys device were compared with invasive measurements. Results: A total of 25 patients were included. Overall, 708 epochs with adequate PPG signal belonging to 17 patients were analyzed. A total of 84% of the SBP estimates and 99% of the DBP estimates have an absolute error of less than 10 mmHg compared with the invasive measurements. Mean difference was 2.3 ± 7.0 mmHg and 0.5 ± 3.5 mmHg for SBP and DBP, respectively. Conclusion: The Senbiosys device is accurate enough to determine BP in a selected population undergoing coronary angiography.